The hottest July day on the railway network: insights and thoughts for the future. (26th September 2017) - Ferranti, Emma; Chapman, Lee; Lee, Susan; Jaroszweski, David; Lowe, Caroline; McCulloch, Steve; Quinn, Andrew
ABSTRACT: The 1 July 2015 was the hottest July day on record (37.5 °C recorded at Heathrow Airport) in the United Kingdom (UK), and record‐breaking temperatures were recorded across England. This short‐duration heatwave (30 June–1 July 2015) affected railway services both directly, by causing asset failure or malfunction, and indirectly, by necessitating the use of emergency speed restrictions (ESRs) to reduce the likelihood of track buckling. Incidents caused by heat and lightning were recorded across the British railway network, and knock‐on delays affected rail travel in regions where extreme weather did not have a direct impact. Over both days there were more than 220 000 delay‐minutes. Many of these could not be attributed specifically to the weather, but 23 700 delay‐minutes were due to emergency speed restrictions (ESRs) as a preventative measure to reduce the likelihood of rail buckling, 12 800 to heat and 4000 to lightning incidents. All regions experienced more than twice the daily average delay‐minutes on one or both days, costing an estimated £16 million to the national economy. Incidents on critical routes (e.g. London North Eastern connecting London and Scotland) or near critical transport nodes such as Manchester Piccadilly caused the longest delays. Under future warmer climatic conditions, heatwaves and extreme temperatures are projected to occur more frequently and the railway operator has several measures to adapt or update existing infrastructure in order to reduce the impact of heat and lightning. Alternative solutions such as low‐cost sensors for real‐time condition monitoring or green infrastructure for increased asset resilience should also be considered. Abstract : The 1 July 2015 was the hottest July day on record in the UK. This short‐duration heatwave (30 June–1 July 2015) directly affected railway services causing infrastructure failures and/or necessitating emergency speed restrictions. Incidents caused by heat and lightning were recorded across the British railway network and knock‐on delays affected rail travel in regions where extreme weather did not have a direct impact. There were nearly 220 000 delay‐minutes recorded on 30 June–1 July costing an estimated £16 million to the national economy.